(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Mobility (including desorption-absorption) of heavy metals in sediments varies depending on the chemical properties of sedimentary minerals in which the metals are associated and hence possibly differentiate their origin (natural and anthropogenic). This study aims to reveal on Cu and Fe of origin based on their chemical fractionation and total concentration. The study location consisted of 11 points clustered into three parts i.e the east coast, west coast, and Nias Island of North Sumatra. The geochemical fraction was obtained based on the SEP BCR (Sequential Extraction Process Bureau Reference of the European Commission) multilevel procedure in four phases: acid dissolved fraction, reduced fraction, oxidation fraction, and residual fraction. The total metal determination was based on the USEPA 3050B method. Metal concentration determination were carried out using atomic absorption spectrophotometry (AAS). The results showed that anthropogenic activities suspected of contributing Fe metal to sediment were higher indicated by non-residual concentrations (5.55-203.15 mg/kg) than the residual fraction (4.89-21.47 mg/kg). In contrast to Cu, the highest association in the sediment is the residual fraction (2.24-8.85 mg/kg). These metal apparently were derived from both natural and anthropogenic sources. Heavy metals in sediments have contributed from natural and anthropogenic sources, Cu is thought to have more natural sources and Fe is thought to originate predominantly from human activities both around the coast and possibly from the land.